1802 N.Y. Laws 41-42 - (:unkn) unknown (My University, 1785)
Ch. 81: Whereas great dangers have arisen, and mischief been done by the pernicious practice of firing guns, pistols, rockets, squibs, and other fire-works, on the eve of the last day of December, and first and second days of January: For prevention whereof for the future: Be it enacted by the People of the State of New York, represented in the Senate and Assembly, and it is hereby enacted by the authority of the same, that if any person or persons whomsoever, shall fire or discharge any gun, pistol, rocket, squib or other fire-work, within a quarter of a mile of any building, on the said eve or days before mentioned, every such person or persons so offending and being thereof convicted before any justice of the peace of the city or county where such offense shall be committed, either by the confession of the party or parties so offending, or the oath of any one credible witness, shall for every such offence, forfeit the sum of forty shillings
Keywords: DISCHARGE